Vox Populi Vox Dei - Sofi, Utari Nur (Maliki Interdisciplinary Journal, 2024)
This article discusses the concept of Vox Populi, Vox Dei, meaning "The Voice of the People is the Voice of God," as a principle reflecting the power of public opinion in shaping policies and influencing governmental decisions. Through historical, social, and political analysis, this article explores how the voice of the people has been used as a tool to strengthen democracy, along with the challenges in preserving the authenticity and representation of public voices in the modern era. With the rise of social media and digital platforms, public opinion has gained more prominence, yet it is often distorted by particular interests. This article also highlights the importance of political literacy and active civic engagement in the democratic process so that Vox Populi, Vox Dei truly benefits society and serves as the foundation for fair and transparent governance.